2018
DOI: 10.1128/aac.02593-17
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Basis of pH-Dependent 5-Flucytosine Resistance in Aspergillus fumigatus

Abstract: 29The antifungal drug 5-flucytosine (5FC), a derivative of the nucleobase cytosine, is 30 licenced for treatment of fungal diseases however it is rarely used as a monotherapeutic 31 to treat Aspergillus infection. Despite being potent against other fungal pathogens, 5FC 32 has limited activity against A. fumigatus when standard in vitro assays are used to 33 determine susceptibility. However, in modified in vitro assays where the pH is set to pH 34 5 the activity of 5FC increases significantly. 35Here we provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…Plate growth-based susceptibility testing revealed that, similar to previous work (Gsaller et al 2018), 5FC levels ≥ 10 μg/ml blocked wt growth at pH5, while 100 μg/ml 5FC were required at pH7 (Fig. 1b).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Plate growth-based susceptibility testing revealed that, similar to previous work (Gsaller et al 2018), 5FC levels ≥ 10 μg/ml blocked wt growth at pH5, while 100 μg/ml 5FC were required at pH7 (Fig. 1b).…”
Section: Resultssupporting
confidence: 85%
“…Inactivation of each of these steps resulted in 5FC resistance, whereby inactivation of Fur1p also conferred 5FU resistance (Kern et al 1990). Orthologous proteins from S. cerevisiae (Fcy2p), A. fumigatus and Aspergillus nidulans (FcyB), respectively, have been identified as major cellular 5FC importers (Paluszynski et al 2006; Vlanti and Diallinas 2008; Gsaller et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The repeat is 34-, 46-, or 53-bp long and located approximately 300 bp upstream of the cyp51A start codon. The region contains AtrR-and SrbA-binding elements [6][7][8] , which regulate cyp51A expression. In addition to the duplication of the region upregulating cyp51A expression, amino acid substitutions contribute to azole resistance, except in the TR53-type strain, which contains no substitution in cyp51A.…”
Section: Emergence Of Azole-resistant a Fumigatus In The Environmentmentioning
confidence: 99%